Phototherapy-Induced Hypocalcemia in Icteric Term Neonates - Naghmana, .; Liaqat, Israr; Huma, .; Tarum, . (Biological and Clinical Sciences Research Journal, 2025)
Neonatal jaundice requiring phototherapy is a common condition, but phototherapy has been associated with potential side effects, including hypocalcemia. Understanding the frequency and risk factors of phototherapy-induced hypocalcemia can aid in its prevention and management. Objective: This study aimed to determine the frequency of phototherapy-induced hypocalcemia in icteric term neonates and assess its association with demographic and clinical factors. Methods: A prospective cross-sectional study was conducted in the emergency department of a tertiary care hospital. After obtaining ethical board approval and informed parental consent, 150 term neonates with hyperbilirubinemia requiring phototherapy were enrolled from 26 July 2024 to 26th January 2025. Demographic data, including age, gender, birth weight, gestational age, and bilirubin levels at presentation, were recorded. Blood samples were collected before and after 48 hours of phototherapy to assess serum calcium levels. Hypocalcemia was defined as a serum calcium level <8.4 mg/dL. Data were analysed using SPSS version 25, with statistical significance set at p ≤ 0.05. Results: The mean age of neonates was 2.41 ± 0.80 days, with a birth weight of 3.08 ± 0.80 kg and a gestational age of 37.77 ± 1.25 weeks. The mean bilirubin level at presentation was 22.62 ± 1.34 mg/dL, and the average duration of phototherapy was 31.97 ± 9.26 hours. Of the enrolled neonates, 54.7% were male, and 45.3% were female. Phototherapy-induced hypocalcemia occurred in 26.7% of cases. Stratification by age showed hypocalcemia rates of 17.5% in 1-day-old, 12.5% in 2-day-old, and 70% in 3-day-old neonates, though the differences were not statistically significant. Hypocalcemia was more frequent in neonates with bilirubin levels >21 mg/dL and those requiring prolonged phototherapy, though these findings also lacked statistical significance. Conclusion: Phototherapy-induced hypocalcemia is a notable concern in neonates undergoing treatment for hyperbilirubinemia. While no statistically significant associations were observed with age, gender, or gestational age, neonates with higher bilirubin levels and prolonged phototherapy appear to be at greater risk. Close monitoring of calcium levels in these neonates is recommended to prevent complications and improve patient outcomes.